Beyond the boundaries of physical education : educating young people for citizenship and social responsibility - Laker, Anthony, 1951- (Routledge/Falmer Press, 2000)
"Beyond the Boundaries of Physical Education sets out to celebrate physical education and sport and highlight its potential benefit for individuals, communities and society as a whole. By doing this, it is hoped to encourage the educational establishment to embrace the subject area as a vehicle for the complete development of the individual."--Jacket